If
x
x
x
1
6
=
1
6
,
then evaluate
x
x
x
1
2
.
Note: x is a real number.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Could you explain more your first step ?
If x^x^x^16 = 16, that means x^16 = 16. That's the only way to get the iterative result x^x^x^16 = x^x^16 = x^16 = x. Hence x = 2^(1/4) and we can determine x^x^x^12 = x^x^2^3 = x^x^8 = x^2^2 = [2^(1/4)]^4 = 2. Very simple. But I did get it wrong the first time!
People, note that the question is not the value of "x" but x^x^x^12 that results in 8. In the first assumption, x^x^x^16=16, if x=2 we never get the result!!!!!! Nelson ([email protected])
Log in to reply
Well the value of x is around 1.185. x^x^x^12 doesn't result in 8.
Please consider the following infinite power tower:
y = x x x x …
x y = x x x x … = y
x x y = x x x x … = y
x x x y = x x x x … = y
Let y = 1 6 and we have the following identity:
x x x 1 6 = x 1 6 = 1 6 ⟹ x = 1 6 1 6 1 = 2 4 1
Finding our value of x x x 1 2 :
x 1 2 = ( 2 4 1 ) 1 2 = 2 4 1 2 = 2 3 = 8
x x 1 2 = ( 2 4 1 ) 8 = 2 4 8 = 2 2 = 4
x x x 1 2 = ( 2 4 1 ) 4 = 2 4 4 = 2 1 = 2
Shouldn't you explain that for y to converge, x must be in a certain interval? And x 1 6 = 1 6 ⇒ x = 1 6 1 / 1 6 is not entirely accurate.
Log in to reply
Actually, we don't need to state the interval of convergence. While I happen to know that the interval is x ∈ [ e − e , e e 1 ] , our value of x that we choose will end up in this range by default! We have picked our value of y so that the infinite power tower does converge, it converges to y. Since the tower converges to y, we know it must be within our interval of convergence, even if we don't know what that interval is. I will, however, note that the tower cannot attain values less than e 1 (because this is the value achieved by our lower bound), but seeing as y is well above this, we have no reason to worry. On the note about why there are multiple real solutions for x, if choosing a different value of x resulted in a different value for x x x 1 2 , then your problem would have multiple solutions, and as I'm sure you know we can't post problems with more than one solution ;)
Log in to reply
Well, since you're using an infinite power tower approach, you should show that it's only defined for the given range of x as you mentioned, as it's a fallacy to make the assumption that there exist a solution.
Just because I posted this question does not give you a green light to say that this problem is actually valid. Unless I further stated that there exist a value of x that satisfy the given equation, then it's alright.
Somemore, you need to show that for all values of x yields the answer of 12, not just because of one particular value of x . Yes, I know I'm being pedantic.
And yes, I thought of using the same approach when solving this problem. We think alike!
Log in to reply
@Pi Han Goh – True, I hadn't considered the possibility that there could be multiple solutions that we hadn't seen yet, I think you're safe for now though haha
It's actually unbelievable how alike we think because I was literally working on a problem to post involving the infinite power tower (which I'll be posting today by the way) when I saw your problem! Even crazier, during my research for the problem I came across this webpage , check out the post at the bottom ;)
Log in to reply
@Garrett Clarke – That's odd, that person's name looks very familiar. ^_^
Log in to reply
@Pi Han Goh – This Y!A problem was posted 4 years ago. I know who gianlino is (one of the very best), but I am not too familiar with Mr G.
Log in to reply
@Michael Mendrin – Haha no that's not what I was referring to, @Pi Han Goh answered the question at the bottom 4 years ago as well, I just happened to see his name and thought he might like the throwback!
Log in to reply
@Garrett Clarke – ? Pi Han Goh is Gohpihan? Oh! I hadn't made the connection before. Both are familiar faces to me, but I didn't realize it's the same person. Hi, Pi. Or, hi pi.
Thanks for explaining
People, note that the question is not the value of "x" but x^x^x^12 that results in 8. In the first assumption, x^x^x^16=16, if x=2 we never get the result!!!!!! Nelson ([email protected])
Log in to reply
DearNelson value of x isn't 2. We have x^4 = 2, i.e. x = 2^1/4.
People, note that the question is not the value of "x" but x^x^x^12 that results in 8. In the first assumption, x^x^x^16=16, if x=2 we never get the result!!!!!! Nelson ([email protected])
I solved the problem using the bisection method starting with initial values 1.1 and 1.2, This gives the correct answer. Here is the Matlab code.
But how you know that the answer is EXACTLY equals to 2?
Log in to reply
Well, according to my solution, I don't know if there is a proof that the answer is definitely an integer since I rely on getting the value of x (which is a real number obtained to some accuracy depending on the threshold).
However the answer on Matlab is 2 . 0 0 0 0 0 0 e + 0 0 0
Log in to reply
The exact answer for x is ± 2 1 / 4 .
I don't constitute your code as a proof, but it's something unexpected. I'm curious: is there a faster way to obtain a good approximation? That is, is there an algorithm better than bisection method that works faster than this?
Log in to reply
@Pi Han Goh – Well if this is converted into an equation with a zero, then how about the secant method?
Log in to reply
@Jack Lam – I'm not sure which method you're referring to. Can you elaborate on it?
Log in to reply
@Pi Han Goh – Oh, I just realised that Newton's method would work better, but the Secant method is essentially the finite difference version of Newton's method (think finite differences instead of infinitesimal differences, and the limit definition of a tangent)
@Pi Han Goh – can we take the value of -2^(1/4) ? as the problem says, solve for real value of x.
Log in to reply
@Sanjoy Roy – Yes. Why not?
Log in to reply
@Pi Han Goh – i am unable to find that negative value.
Log in to reply
@Sanjoy Roy – I've already given you the answer: − 2 1 / 4 .
How can we determine value of low and high?
Suppose we define x^x^x = y, so the problem becomes: if y^16 = 16, what is y^12? If y^16 = 16, 16*log(y) = log(16), and log(y) = [log(16)/16 = .0752575, so y = 10^(.0752575) = 1.189207118. Then y^12 = (1.189207118)^12 = 2^3 = 8. Ed Gray]
Log in to reply
You got the rules of exponents wrong. See How are exponent towers evaluated?
So my method might be a little peculiar but I hope it makes sense. At first, I looked at the left side of the equation and the first thing that immediately popped into my head was 'well 2 2 2 makes up 1 6 ' but that obviously did not cater to the 1 6 t h power. So the next thought was to substitute a value in to x that would make the LHS of the equation equal to 1 6 . 'What if I let x equal to some power of 1 6 ?' And that is what I did. I substituted 1 6 1 6 1 in place of x . The LHS essentially became
1 6 1 6 1 × 1 6 1 6 1 × 1 6 1 6 1 × 1 6
Well, great! The LHS now equals to the RHS, i.e. 1 6 .
The next part was easier to calculate. Simply substitute 1 6 1 6 1 in to the equation x x x 1 2 and solve to get RHS = 2 .
Great try, but it's not correct. You need to show that for ALL x satisfying the given constraint, the x x x 1 2 is always equals to 2.
Let y = x 1 6 , t h e r e f o r e x = 1 6 y H e n c e i f x x x 1 6 = 1 6 , ( 1 6 y ) ( 1 6 y ) y = 1 6 T a k i n g t h e l o g a r i t h m t o t h e b a s e 1 6 y o n b o t h s i d e s y i e l d s ( 1 6 y ) y l o g 1 6 y 1 6 y = l o g 1 6 y 1 6 ⇒ ( 1 6 y ) y = l o g 1 6 ( 1 6 y ) l o g 1 6 1 6 ⇒ ( 1 6 y ) y = 1 6 1 l o g 1 6 y l o g 1 6 1 6 ( 1 6 y ) y l o g 1 6 y = 1 6 , w h i c h m e a n s t h a t , y ( 1 6 y ) y = 1 6 1 6 b u t ( 1 6 y ) ( 1 6 y ) y = 1 6 , i m p l y i n g t h a t [ ( 1 6 y ) ( 1 6 y ) y ] 1 6 = 1 6 1 6 = y ( 1 6 y ) y W e c a n t h e s a f e l y s a y t h a t ( y 1 6 y 1 6 y ) 1 6 = y y 1 6 y ⇒ 1 6 × ( 1 6 y 1 6 y ) = y 1 6 y , lo g y 1 6 + 1 6 y ( lo g y y − lo g y 1 6 ) = 1 6 y T h e r e f o r e , ( 1 − 1 6 y ) lo g y 1 6 = 0 , i m p l y i n g t h a t t h e a n s w e r i s e i t h e r y = 1 6 , o r t h e n o t v e r y i m p r a c t i c a l lo g y 1 6 = 0 s o y = x 1 6 = 1 6 ⇒ x = 1 6 1 6
There's another solution: x = − 1 6 1 6 .
Will you please elaborate the first portion of 3rd line from the last ?
At first I got it wrong (8) since I was not familiar with the tetration, after looking it up I still am not sure how to get the 2 algebraically, I did get it numerically, in MATLAB it's pretty simple:
sol=fsolve(@(x)x^(x^(x^(16)))-16,1) %(=1.1892)
sol_final=sol^(sol^(sol^12)) %(=2)
However you have to be carefull with the use of parenthesis, if you give matlab:
sol2=fsolve(@(x)x^x^x^16-16,1) %(=1.1421)
sol_final2=sol2^sol2^sol2^12 %(=8)
Thank you for your solution. You're absolutely right.
Well, I got the right answer, but I made the same dumb mistake as a couple of others did below, and just lucked into it. Is there a way to re-cast this problem so that you can't luck into the answer by just saying, "Oh, x x x 1 2 is the 4th root of x x x 1 6 , so the answer must be 2." That is clearly not a generally correct statement, since ( x x x 1 2 ) 4 = x 4 ( x x 1 2 ) , and 4 ( x x 1 2 ) = x x 1 6 ONLY in the case where x = ± 2 4 1 , as in this problem.
Unfortunately no. But thanks for the attempting this problem! Hope you enjoyed it!!
Given x^x^x^16 = (x^x^x^12)^(x^4) =16 We now simply take the 4th root of the both sides of the equation which gives us x^x^x^12=2
So the square root of 2 2 1 1 0 0 is 2 2 1 1 0 0 − 2 ?
I really don't understand this solution! Could you explain?
X^X^X^16 = 16 and X^X^X^12 = ?
So X^X^X^12^4 = 16 and ?^4 = 16 thus ? = 16^1/4 which is 2
So the square root of 2 2 1 1 0 0 is 2 2 1 1 0 0 − 2 ?
If x^x^x = y, then y=16^1/16 (good). Therefore y^12 = 16^(12/16) = 8 WRONG! Remember that y = x^x^x and that equals 16^(12/16), so x = 2
Wrong. You can't just apply 16th root to both sides of the equation. a b c = a b × c is not true.
Log in to reply
i got the answer as 8. what's wrong with my answer?
Problem Loading...
Note Loading...
Set Loading...
We change the equation as follows: x x x 1 6 = x 1 6 ( 1 6 x 1 6 ( 1 6 x 1 6 ) ) = 1 6 Then we replace x 1 6 with y : y ( 1 6 y ( 1 6 y ) ) = 1 6
if we elevate to the power of 1 6 both side of the equation then we have y y ( 1 6 y ) = 1 6 1 6 . It is trivial to see that the equation holds for y = 1 6 . Thus, x x x 1 2 = x x 1 6 1 6 1 2 = x 1 6 1 6 8 = 1 6 1 6 4 = 2